Integrated Scheduling Optimization for Multi-Line Production and Transportation of Prefabricated Components Considering Shared Resources - Yiran Dan; Chengshuang Sun; Qianmai Luo (Buildings)
With the increasing popularity of prefabricated buildings, more and more precast plants have been equipped with multiple production lines to increase productivity and meet the growing market demand. Sharing equipment, human, and transportation resources is a typical feature of integrated scheduling management for precast production and transportation on multiple production lines. In response to these characteristics, this article studies the integrated scheduling optimization of multi-line production and transportation for prefabricated components. With on-time delivery and lower costs as the goals, a scheduling optimization mathematical model is established for this scenario. This article adopts the genetic algorithm to design the solution algorithm for this model, and the effectiveness of the model and algorithm is verified through an example. The results show that compared with the traditional scheduling scheme, this method can prominently reduce costs while promoting on-time delivery. The model and method can help the precast plant with multiple production lines improve efficiency and reduce costs, as well as enhancing the practicability of the precast production and transportation scheduling scheme.